Two symbiotic bacteria of the entomopathogenic nematode Heterorhabditis spp. against Galleria mellonella. (1st March 2017) - Liao, Chunli; Gao, Along; Li, Bingbing; Wang, Mengjun; Shan, Linna
Abstract: The entomopathogenic nematode Heterorhabditis spp. is considered a promising agent in the biocontrol of injurious insects of agriculture. However, different symbiotic bacteria associated with the nematode usually have different specificity and virulence toward their own host. In this study, two symbiotic bacteria, LY2W and NK, were isolated from the intestinal canals of two entomopathogenic nematode Heterorhabditis megidis 90 (PDSj1 and PDSj2) from Galleria mellonela, separately. To determine their species classification, we carried out some investigations on morphology, culture, biochemistry, especially 16S rDNA sequence analyses. As a result, both of them belong to Enterobacter spp., showing the closest relatedness with Enterobacter gergoviae (LY2W) and Enterobacter cloacae (NK), respectively. Moreover, the toxicity to Galleria mellonella was examined using both the metabolites and washed cells (primary and secondary) of these two strains. The results indicated both metabolites and cells of the primary-type bacteria could cause high mortalities (up to 97%) to Galleria mellonella, while those of the primary-type bacteria only killed 20%. These findings would provide new symbiotic bacteria and further references for biological control of the agricultural pest. Highlights: Two symbiotic bacteria (LY2W and NK) of entomopathogenic nematode were obtained. Strains LY2W and NK were identified as Enterobacter gergoviae and Enterobacter cloacae, respectively. These two strains showed high virulence to Galleria mellonella. The primary type strains caused significantly higher mortalities to G. mellonella.